Quaternary development of resilient reefs on the subsiding kimberley continental margin, Northwest Australia - Collins, Lindsay; Testa, V. (Universidade de Sao Paulo * Instituto Oceanografico, 2010)
The Kimberley region in remote northwest Australia has poorly known reef systems of two types; coastal fringing reefs and atoll-like shelf-edge reefs. As a major geomorphic feature (from 12ºS to 18ºS) situated along a subsiding continental margin, the shelf edge reefs are in a tropical realm with warm temperatures, relatively low salinity, clear low nutrient waters lacking sediment input, and Indo-West Pacific corals of moderate diversity. Seismic architecture of the Rowley Shoals reveals that differential pre-Holocene subsidence and relative elevation of the pre-Holocene substrate have controlled lagoon sediment infill and reef morphology, forming an evolutionary series reflecting differential accommodation in three otherwise similar reef systems.The Holocene core described for North Scott Reef confirms previous seismic interpretations, and provides a rare ocean-facing reef record. It demonstrates that the Indo-Pacific reef growth phase (RG111) developed during moderate rates of sea level rise of 10 mm/year from 11 to about 7-6.5 ka BP until sea level stabilization, filling the available 27 m of pre-Holocene accommodation. Despite the medium to high hydrodynamic energy imposed by the 4m tides, swell waves and cyclones the reef-building communities represent relatively low-wave energy settings due to their southeast facing and protection afforded by the proximity of the South Reef platform. This study demonstrates the resilience of reefs on the subsiding margin whilst linking Holocene reef morphology to the relative amount of pre-Holocene subsidence.